PENCEGAHAN PENYAKIT ASAM URAT SERTA PEMAHAMAN TENTANG OBAT DAN POLA PERUBAHAN GAYA HIDUP YANG TEPAT DALAM RANGKA PENCAPAIAN PEDULI KESEHATAN - sujana, Dewa Gede; Ramatillah, Diana Laila (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
Gout is a disease that many people suffer from, many people do not comply with treatment and avoid foods that cause gout. The aim of this outreach is to educate the public so they can use appropriate treatment for gout. This counseling was carried out directly at the Sunter Agung 1 Community Health Center with 27 participants. From this counseling, it was found that the number of female participants was 21 people, and 6 male participants, the first group ranging from 18 years to 44 years old, the second group 45-64 years old and the third group <65 years. From this counseling, 85% of the post test score was obtained. It can be concluded that the data shows that the public already understands gout and its treatment, which is known from the posttest results.